ON SOME ASPECTS OF THE CLASSIFICATION OF CRUMPLE CERVICAL SCAR - F. F. Badretdinova; V. B. Trubin; A. G. Khasanov (Акушерство, гинекология и репродукция, 2016)
Of the significant variation in the frequency of cervical strain caused by the scar with a mixed assessment of traumatic deformities on examination did not reflect the degree of scar deformities. This is facilitated by the shortcomings of the existing classification, which unfortunately did not affect the volume of surgical tactics and does not take intoaccount newly emerging pathological conditions of the mucous membrane. In view of the above, the authors proposed to supplement the existing classification of scar deformities of the cervix, which allow you to develop standard approaches to the treatment, depending on the degree of deformation and the reproductive function of women. Scar deformity of 1degree of old single or multiple lateral cervical tears up to 2 cm deep. Cervical canal is partially preserved and is a cone with vertex at the internal OS. Eversion of cervical mucous is usually limited to the bottom of its Division. Scar deform of 3 degree-old tears reaching to the body of the uterus with assymetric hypertrophy of lip dystopic cervix in combinationwith dysplasia and HPV. SCAR deformation degree 4-old tears reaching to the body of the uterus, combined with the failure of the pelvic floor.